2005
DOI: 10.7326/0003-4819-142-2-200501180-00009
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Therapy for Cirrhotic Hepatitis C: Association with Reduced Hepatocellular Carcinoma Development and Improved Survival

Abstract: Interferon therapy for cirrhotic patients with chronic hepatitis C, especially those in whom the infection had been cured, inhibited the development of hepatocellular carcinoma and improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
218
3
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(236 citation statements)
references
References 32 publications
12
218
3
3
Order By: Relevance
“…In the interferon era, antiviral therapy in patients with cirrhosis was associated with reduced hepatocellular carcinoma [9]. Large cohorts such as HALT-C have demonstrated that reduced cancer development may be an effect of interferon, which has anti-tumour properties, rather than viral clearance alone, although this was only observed after four years from treatment [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the interferon era, antiviral therapy in patients with cirrhosis was associated with reduced hepatocellular carcinoma [9]. Large cohorts such as HALT-C have demonstrated that reduced cancer development may be an effect of interferon, which has anti-tumour properties, rather than viral clearance alone, although this was only observed after four years from treatment [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of interferon-based therapies have demonstrated that HCV clearance improves liver fibrosis, even in cirrhosis [7]. Moreover, patients who achieved SVR had reduced mortality, complications of cirrhosis and hepatocellular carcinoma compared to untreated patients or those who failed to achieve SVR [8][9][10]. However such studies involved patients with relatively 'early' cirrhosis and it remains unclear whether these long term benefits will be seen in patients treated for more advanced disease.…”
Section: Introductionmentioning
confidence: 99%
“…9 A retrospective analysis and a prospective study of patients followed up for 6.8 years conducted in Japan showed that HCC risk was reduced, but not abolished, in patients with cirrhosis. 5,25 However, the overall reduction in HCC risk in SVR cirrhotic patients was limited as it did not exceed 20% with respect to untreated or non-responder patients. 14,15 A clear-cut relationship between SVR and drop of HCC risk in Caucasian patients with cirrhosis has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…After the meta-analyses, 3 observational cohort studies, two prospective studies conducted in Japan [32] and in Taiwan [33] and one retrospective study conducted in Italy [34], have clearly confirmed that the efficacy of IFN in the chemoprevention of HCC is exclusively linked to the achievement of a sustained viral eradication, while no benefit in reducing HCC development was observed in non-responder patients.…”
Section: Secondary Preventionmentioning
confidence: 92%